Peran Orangtua dalam Mendukung Kesiapan Sekolah Anak; Transisi PAUD-SD/MI - Mahfuzah, Ainun; Salhah (Program Studi PGMI STAI Al Falah Banjarbaru, 2025)
This study aims to analyze the role of parents in supporting children’s school readiness during the transition from early childhood education (PAUD) to primary school. School readiness is a multidimensional construct that includes children’s social-emotional maturity, language and cognitive development, motor and self-care abilities, as well as their capacity to engage within the learning environment. However, several misconceptions remain prevalent in society, such as assuming that age and early literacy-numeracy skills are the main indicators of school readiness. This study employs a literature review method by examining recent empirical findings, national policies on PAUD–primary school transition, and theoretical frameworks related to parental involvement in early childhood education. The analysis indicates that parental engagement across five foundational domains—spiritual and moral development, social and language competence, emotional maturity, cognitive readiness, and motor and self-care skills—is crucial in helping children adapt effectively to primary school settings. Parents play an essential role in providing stimulation, establishing routines, offering emotional support, and fostering moral values and independence during the early years of schooling. The findings highlight the importance of strengthening parents’ understanding of holistic school readiness and promoting collaboration among families, schools, and educational policies to support a smooth PAUD–SD/MI transition.